Anisotropy of the magnetic correlation function in the inner heliosphere - Ruiz, M.E. (2010)
For over four decades, low frequency plasma and electromagnetic fluctuations have been observed in the solar wind (SW), making it the most completely studied case of magnetohydrodynamic turbulence in astrophysics, and the only one extensively and directly studied using in situ observations. Magnetohydrodynamic scale fluctuations in the SW are usually anisotropic with respect to the local mean magnetic field (B0). In this work, we present a study of turbulent properties in the inner heliosphere (solar wind between 0.3 and 1 AU) based on modeling in situ plasma and magnetic observations collected by Helios 1 and Helios 2 spacecraft throughout a solar minimum. We present preliminary results on the evolution of the spatial structure of the magnetic self-correlation function in the inner heliosphere. In particular we focus on the evolution of the integral length scale (λ) for magnetic fluctuations and on its anisotropy in the inertial range. As previously known from different studies, we confirm that near Earth λ ∥>λ⊥ (with λ∥ and λ⊥ representing the integral length in the parallel and perpendicular directions respect to B0, respectively). However, for lower distances to the Sun we found that λ∥<λ ⊥. Results presented here will help us to refine models used to describe the turbulence and waves activity in the inner heliosphere. © 2010 American Institute of Physics.